IMPLEMENTASI PROGRAM JUM’AT BERSIH UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN IPA KOMPETENSI DASAR PENANGANAN DAN PENGELOLAAN LIMBAHSISWA KELAS XI PROGRAM STUDI TATA KENCANTIKAN RAMBUT SMKN 6 SEMARANG TAHUN 2010 - Husen Djunaidi (Jurnal Penelitian Pendidikan, 2011)
Abstract: Student existence at the moment there inclination" lazy" read and study lesson books, even less lesson that has characteristics" complex or very complex", toy a more regular" hp sms-facebook", sleepy moment get lesson, doesn't hastextbook, satisfied in get lesson, student inclined quiet doesn't want to ask, and as it. This class action watchfulness aim increasing will (domein apektif, that is attitude, interest, appreciation), increasing ability and comprehension (domaincognate, that is capacity realize, analyze, and break roblem), increasing student craft (domain psiko-motor) in subject IPA competence base handling and waste management. My cycle classical study watchfulness result is not yet it to, value pree test and post test 95% student must remedial, so that study result in my cycle shows KKM very low (75%). Evaluation result and study reflection in my cycle, study area teacher IPA do completing RPP, furthermore implementation at cleanfriday program activity and cycle study 2 by using communication strategy" multy ways traffic communication" . This study execution result shows: 1) there student will enhanced to carry out teacher action, 2) there ability enhanced and comprehension in competence matter base handling and waste management, so that 98% result value learns student proportionally increase. Value recapitulationresult magister learn class student XI two semester proggram school year hair beauty order 2009 - 2010. Next cycle action 2 can achieve fucus KKM.